The Structural Performance of Fiber-Reinforced Geopolymers: A Review - Salvatore Benfratello; Luigi Palizzolo; Carmelo Sanfilippo; Antonino Valenza; Sana Ullah (Eng)
Geopolymers (GPs), as promising alternatives to ordinary Portland cement (OPC)-based concrete, have gained interest in the last 20 years due to their enhanced mechanical properties, durability, and lower environmental impact. Synthesized from industrial by-products such as slag and fly ash, geopolymers offer a sustainable solution to waste management, resource utilization, and carbon dioxide reduction. However, similarly to OPC, geopolymers exhibit brittle behavior, and this characteristic defines a limit for structural applications. To tackle this issue, researchers have focused on the characterization, development, and implementation of fiber-reinforced geopolymers (FRGs), which incorporate various fibers to enhance toughness, ductility, and crack resistance, allowing their use in a wide range of structural applications. Following a general overview of sustainability considerations, this review critically analyzes the structural performance and capability of geopolymers in structural repair applications. Geopolymers demonstrate notable potential in new construction and repair applications. However, challenges such as complex mix designs, the availability of alkaline activators, curing temperatures, fiber matrix compatibility issues, and limited standards are restricting its large-scale adoption. The analysis and consolidation of an extensive dataset would support the viability of geopolymer as a durable and sustainable alternative to what is currently used in the construction industry, especially when fiber reinforcement is effectively integrated.